Three patterns of osteoarticular involvement in SAPHO syndrome: a cluster analysis based on whole body bone scintigraphy of 157 patients. (8th January 2019) - Cao, Yihan; Li, Chen; Yang, Qiao; Wu, Nan; Xu, Ping; Li, Yueting; Shi, Ximin; Pan, Qingqing; Wu, Xia; Sun, Xiaochuan; Zhao, Yanxue; Gu, Zhaoqi; et al.
Abstract: Objectives: To explore the patterns of osteoarticular involvement in SAPHO syndrome. Methods: Baseline clinical characteristics and imaging data of 99m Tc-MDP whole-body bone scintigraphy (WBBS) were collected from 157 out of 164 patients diagnosed with SAPHO syndrome. The twelve most frequently involved osteoarticular sites were analysed by hierarchical cluster analysis with the Ward minimum-variance method. Results: Three distinctive patterns of osteoarticular involvement were identified: the spinal type (70 patients, 44.6%), with predominantly thoracic, lumbar or sacral vertebral lesions; the costal type (52 patients, 33.1%), with lesions of anterior ribs, particularly the first ribs; and the sternoclavicular type (35 patients, 22.3%), with predominantly sternal and bilateral sternoclavicular lesions, characterized by the typical bullhead sign. Notably, a total of 77 (49%) patients exhibited lesions of ribs on WBBS, of which 61.3% involved the first ribs. Interestingly, patients of spinal type were older at onset of cutaneous manifestations than those of sternoclavicular type ( P = 0.036) and costal type ( P = 0.035). The disease course was remarkably longer in sternoclavicular type than costal type ( P = 0.001) and spinal type ( P < 0.001). Conclusion: The osteoarticular involvement in SAPHO syndrome can be categorized as three distinct patterns with different corresponding clinical features. The costal involvement in SAPHO syndrome, which was under-recognized previously, may define a distinct sub-type of the disease.